A Cross Sectional Survey on Compliance to Antibiotics in Patients with Respiratory Tract Infections in a Tertiary Hospital in Ajman, UAE - Rosalia, Rina; Essam Atta, Nouran; Gebreigziabher, Fithawit Bahran; Salisu, Yahya; Ibrahim Ladan, Mubarak; Shukur, Amna; Burhanuudin Shaikh, Rizwana; Al-Sharbatti, Shatha; Jacob, Shery; Mabrouk, Salwa Abdelzaher (Journal of Pharmacy Practice and Community Medicine)
Background: Compliance to antibiotic regimen is one among several measures required to prevent antibacterial resistance. As there is paucity of published information on compliance to antibiotics in respiratory infections in Ajman, UAE, it is hoped that this study can fill the gap in knowledge. Objectives: 1. To estimate the rate of compliance to antibiotics in patients with respiratory tract infections (RTI). 2. To identify the most frequently prescribed antibiotics for respiratory tract infections. 3. To determine the extent to which certain factors influence the rate of compliance. 4. To identify the most common side effects associated with antibiotic use. Methods: A cross sectional study was carried out using a validated, self-administered questionnaire which addressed socio-demographic characteristics, Medical history and questions on compliance and reasons for non-compliance. Data was analyzed using SPSS version 24 and Chi-square test was used to test the significance of association. A p-value of <0.05 was accepted as a significant level. Results: The study included 260 participants amongst which the majority was men (58.5%). There was no significant association between the socio-demographic characteristics and the compliance pattern of the participants. Among 260 participants, 180 (69.2%) reported that they have had an RTI within the past one year and amidst the 180, 172 (95.6%) respondents have been prescribed an antibiotic for their RTI. There was no significant association between patient compliance and the factors that could possibly affect compliance by contributing to skipping medication doses. Out of 172 respondents, 134 (77.9%) reported that they did not experience any side effects while 38 (22.1%) participants expressed that they had experienced certain side effects with antibiotic use. The most common side effect reported by the participants was diarrhea (20.5%) followed by tiredness and drowsiness (each 10.3%). Conclusion: The participants of the study were found to be mostly compliant to their prescribed antibiotic regimen. There was no significant association between the antibiotic compliance and the socio-demographic characteristics as well as the factors that influence compliance. Majority of the patients were found to be adequately counseled about the importance of antibiotic compliance.
Keywords: Regimen; Therapy; Non-compliance; Compliance; Adherence; Patient counseling; Antibiotics